Teacher’s Strategies in Teaching English for Deafable Students - Wardatus Zahro Wardah; Muhammad Hifdil Islam; Benny Hamdani (Innovative: Journal Of Social Science Research, 2023)
Children with special needs are still social beings who need and need social interaction with other people, this is a form of recognition of their existence, just like other children. Not only that, they also have abilities and intelligence that are not inferior to normal children in general. Children with special needs may face some barriers to attending public schools because of their unique needs. The purpose of this study was to find out the strategies used by teachers at SMP Yayasan Extraordinary Dharma Asih to teach deaf students and overcome the challenges they face. This study uses a descriptive qualitative method that focuses on extracting in-depth and detailed information by collecting various data sources.